Educational Supply Chain Management: A Review Paper - Nur Shahida, Mat Ishah; Lee, Khai Loon; Nawanir, Gusman (Springer, Cham, 2022)
upply chain management (SCM) is relatively not a newly founded area of research. It is rather the underlying theory that always exists in a society without official recognition. However, the concept of educational supply chain management (EduSCM) is still limited. The purpose of this paper is to review the philosophy of SCM in current higher educational institutions (HEIs) in which is hoped to be the foundation for better ideas that can be put into practice for better management of the HEIs. This paper uses a semi-systematic review approach for the acknowledgement of all related literature throughout time and places. According to an exploratory study conducted by one of the researchers, 87% of SCM studies are done in the industrial context, 13% for the service businesses, and the remaining five per cent for the educational sector. However, there is an increase in research trends in the educational sector, indicating a hopeful improvement in a country’s education system. Researchers create a few theories, models and frameworks; in a broad and specific topic to better understand SCM in the educational sector. Each level in the educational supply chain (EduSC) was given a fresh and alternative approach and a new focus. The involvements from a lot of different associates and contributors to an EduSC were considered. There are plenty of opportunities and methods to be studied in the backgrounds and developments of the EduSC, EduSC practices, and attributes related to the EduSC. Failing to address these needs may impede the country’s education quality and the quality of the graduates produced.